A Modified Frequency-Dependent Equivalent Linear Method for Seismic Site Response Analyses and Model Validation using KiK-Net Borehole Arrays. Issue 5 (3rd May 2020) - Huang, Duruo; Wang, Gang; Wang, Chaoyi; Jin, Feng
ABSTRACT: A modified frequency-dependent equivalent linear method (M-FD-EQL) is proposed to improve 1D site response at high frequencies. A combination factor is used to interpolate the strain spectrum between the equivalent linear method (EQL) and the frequency-dependent equivalent linear method (FD-EQL). Extensive validation tests have been conducted to benchmark the proposed method with nonlinear analyses of generic sites, and 383 borehole array data from the KiK-net. Based on model validation, an optimal combination factor of 0.2–0.3 in the M-FD-EQL scheme gives an overall best result, and provides improved site response estimates at high frequencies compared with the EQL and FD-EQL methods.